A Psychological Analysis of the Protagonist's Attitude Change in Jennifer Niven's All The Bright Places - Agustina Purba; Pardi Pardi (JOURNAL OF LANGUAGE, 2026)
This study examines the factors contributing to the protagonist's attitude change in All the Bright Places by Jennifer Niven. The research focuses on how personal experiences and social interactions shape the psychological transformation of the main character. The narrative centers on two adolescents, Violet Markey and Theodore Finch, who struggle with trauma and emotional instability. Violet, in particular, undergoes a significant shift in attitude following the death of her sister, which leads her to become withdrawn and emotionally detached. This study employs a psychological approach to literature, applying Azwar's theory of attitude change to identify influencing factors. A descriptive qualitative method is utilized to analyze textual data in the form of words, phrases, and sentences from the novel. The findings reveal that attitude change is influenced by three key factors: personal experience, the influence of significant others, and emotional factors. Among these, personal trauma and interpersonal relationships emerge as the most dominant factors affecting the protagonist's transformation. This study highlights the complexity of human attitudes and demonstrates how literary works can reflect psychological realities, particularly in the context of adolescent development and coping mechanisms.